One-dimensional confinement and width-dependent bandgap formation in epitaxial graphene nanoribbons - Hrag Karakachian (Nature Portfolio, 2020)
Here, the authors investigate armchair graphene nanoribbons by angle-resolved photoelectron spectroscopy, and show the development of a width-dependent semiconducting gap driven by quantum confinement effects, and an ideal one-dimensional electronic behaviour.